The Japanese sense of beauty - Takashina, Shuji 1932-; Treyvaud, Matt (Tokyo Japan Publishing Industry Foundation for Culture, 2018)
"What makes Japanese art unique? In The Japanese Sense of Beauty, art critic and historian Takashina Sh?auji reflects on the aesthetic and philosophical sensibilities underlying Japanese art throughout its history, from the earliest calligraphy and painted screens to modern masters like Hishida Shunso and Yokoyama Taikan. Along the way, Takashina explores themes such as the relationship between subjective perspective and "flat" composition and the playful intermingling of word and image throughout the plastic arts of Japan. He also offers fresh critical perspectives on many individual artists, including Takeuchi Seih?ao, one of the first to fuse traditional techniques with Western realism, and Takahashi Yuichi, who combined a vivid mastery of texture with deceptively traditionalist compositions. Other essays in this wide-ranging collection touch on everything from the symbolism of Mount Fuji to the ancient music known as gagaku, showing how even the most disparate topics can shed new light on what is essential to Japanese culture. The Japanese Sense of Beauty is an important contribution to the study of aesthetics and cultural history, offering insights that will change the way you think about Japanese art." -- Publisher's description.
I. Word and image : the Japanese aesthetic consciousness -- The Kokin Wakash?au and Japanese aesthetics -- The significance of Imperial Waka anthologies -- Cross the word-image border -- Sori : a plastic sensitivity -- European curves, Japanese Sori -- The plasticity of Hiragana -- Comparing Japanese and Western architecture -- What is a Torii? -- Closeness to nature in Japanese aesthetics -- The four seasons in Japanese painting -- Emoji, Moji-e, and play -- Word and image together -- Chirashigaki and Kaeshigaki -- The uniqueness of Chinese characters in Japan -- Word and image in handcraft design -- Fujiwara no Teika's aesthetics of rejection -- Ariwara no Narihira's "Eight Bridges" -- Ono no Komachi's "Color of the Flowers" -- Word and image separated : text design in the West -- Word and image in comics -- Poems and pictures today -- II. Japanese beauty, Western beauty -- East meets West : forms of expression in Japanese and Western art -- The discovery of Japan's aesthetic consciousness -- The introduction of Western painting techniques to Japan -- Two forms of expression -- The aesthetics of omission and the close-up -- Contrasting principles -- Design in Japanese art -- The dawn of Japanese oil painting -- Sentiment and sensibility : beneath the surface of Wasei Yuga -- Japan and the West in the art of Takeuchi Seih?ao -- III. Roots of the Japanese aesthetic consciousness -- Word and image -- Chinese characters and the Japanese language -- The culture of name succession -- The aesthetics of the margin -- Postcards and place -- Gagaku without Gagaku -- Canonical beauty and situational beauty -- Taikan and Fuji -- Whither Passing Spring? -- School songs and musical education -- Fukuzawa Yukichi, traditionalist -- Blossoms of devotion : Goshun, Buson, and the white plum -- Dragons, tigers, and museums -- Interpretation as transformation -- Interpretation as creative act -- Bridges and the Japanese -- The glittering vague -- Travel, east and west -- Tokyo Station and the culture of travel -- Robots and Japanese culture -- Mount Fuji as world cultural heritage.
"Originally published in Japanese under the title of Nihonjin ni totte utsukushisa to wa nanika by Chikumashobo Ltd., in 2015"--title page verso.
Includes bibliographical references.
Keywords: Aesthetics, Japanese; Arts, Japanese -- Philosophy; Art, Japanese -- Philosophy